Customer satisfaction and the influence of quality service aspects: A case study of a cooperative union in Cape Coast, Ghana's Central Region - Godson Kwame Amegayibor; Clara Operabea Korankye (Annals of Management and Organization Research, 2021)
Purpose: This is to determine the association between quality service aspects and customer satisfaction in non-interest-based financial services. Research Methodology: The study used a quantitative approach and a descriptive design, as well as a simple random sampling technique, closed-ended questionnaire, multiple linear regression, and SPSS 20.0 versions for data translation and analysis. Result: The study concludes that customer satisfaction is influenced by quality service dimensions such as empathy, tangibility, assurance, responsiveness, and reliability. Limitation: Time limits, assumptions about the underlying theory, and the use of a single credit union were all possible stumbling blocks. Limitations: Time limits, assumptions about the underlying theory, and the use of a single credit union were all possible stumbling blocks Contribution: The contribution is that in a highly active, dynamic, and competitive business environment, organizations must ensure employee effectiveness and efficiency because their efforts will execute quality service dimensions. Customers' disconfirmation or confirmation is heavily influenced by the organization, employees, and environment created to meet their expectations.